The Need to Develop Effective Conservation Strategies for Indigenous Animal Genetic Resources (AnGR) in Africa: Policy Brief 17 - African Union Inter-African Bureau for Animal Resources; AU-IBAR (AU-IBAR, 2019)
The policy brief highlights three (3) key messages: (i) conservation enables us to keep AnGR which have unique and beneficial attributes to mitigate unpredictable future situation like climate change; (ii) Conservation helps us to maintain our heritage like culture, values and prides associated with the genetic resources; (iii) Conservation needs to be linked with sustainable utilization. This policy brief was made possible through financial support provided by the European Union (EU) funded Project “Strengthening the Capacity of African Countries to Conservation and Sustainable Utilisation of African Animal Genetic Resources.''
Keywords: Climate Change; Animal Genetic Resources